A NETWORK-BASED METHOD FOR CONSTRUCTING A TECHNOLOGY ROADMAP - Huang, Jia-Yen; Lee, Chun-Lin (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
Technology roadmaps are essential for technology management, but current roadmaps that use text mining to build new processes are time-consuming and laborious. In particular, the identification of relationships between different layers of roadmaps mainly relies on experts. To remedy this problem, this study proposes a systematic and objective process for constructing a technology roadmap. First, by integrating the Stanford parser and a co-word analysis method, we develop a modified Stanford parser-based method to select two-word technological terms, which is suitably comprehensive and complete for building a technology roadmap. Second, we innovatively integrate patents, products, and keywords into the same matrix, thus generating an incidence matrix of products and technologies. Based on this matrix, products and technologies can be directly linked to construct a two-layer product technology roadmap without the assistance of experts. We recommend applying a technology lifecycle to estimate the development time of technologies on the technology roadmap timeline, which is an important but often ignored issue. Finally, we provide an example of cloud computing-related products to demonstrate how the proposed technology roadmap approach can provide managers with a competitive technology and product development strategy.